ANALISIS PENGARUH TRUST, PRICE, BRAND IMAGE, SERVICE QUALITY, DAN CUSTOMER SATISFACTION TERHADAP PURCHASE INTENTION PELANGGAN KEDAI MINUMAN BOBA - Usep Suhud; Raza Wardani; Faunillah Oktavia; Shofiyah Azizah Ali (Prodi S1 Ilmu Komunikasi, Fakultas Ilmu Sosial, Universitas Negeri Jakarta, 2022)
This research was conducted to examine what influences the purchase intention of customers when buying a boba drink product